Intellectual Production on Human Rights Archives in the Scopus and Web of Science Data Sources. (2018 – 2023) (Ágora de Heterodoxias, 2024)
The intellectual production on human rights archives from the Scopus and Web of Science data sources during the period between 2018 and 2023 is analyzed. The methodology consisted of bibliometric techniques, supported by production indicators. A registration matrix was developed for the collection and processing of data, highlighting as results that the years of greatest production were 2021 and 2022; the most productive institutions are located in the United States, the United Kingdom, and Latin America; the privileged documentary typologies are scientific articles and book chapters. Regarding co-occurrence networks, very important interactions are evidenced between the theme of human rights archives and aspects such as: violence, transitional justice, construction of collective memory, rights of indigenous communities, and refugees. This demonstrates a high potential for the development of an interdisciplinary perspective that broadens the vision of human rights archives. In conclusion, the interest in this topic is highlighted, which places archival knowledge and practices and documentary information in the ethical and socio-political perspective and reaffirms fundamental rights for the construction of citizenships
Keywords: archives; collective human rights; bibliometrics